Exploring the Sustainability Correlation of Value Co-Creation and Customer Loyalty-A Case Study of Fitness Clubs - Lee, Yu-Lung; Pan, Lee-Yun; Hsu, Chin-Hsien; Lee, De-Chih (Sustainability, 2019)
Fitness gyms have been gaining popularity among Taiwanese people, which means growing competitiveness for fitness gym operators and the necessity for an examination on how to maintain customer loyalty. Since workouts may require more coaching and interactions than other types of exercise, this study focuses on whether the increased customer interactions and involvement, which may be achieved when the operator works on developing customer value co-creation behavior, can generate increased customer loyalty toward fitness gyms. On the other hand, customers’regular behavior may influence customers’perceived necessity of interactions and involvement; this may in turn influence the correlation of value co-creation behavior and customer loyalty. Accordingly, regular behavior was employed as the moderating variable in this study. The study used SPSS software version 22.0 and AMOS software version 22.0 to evaluate the data collected. By convenience sampling, it distributed questionnaires to 470 subjects, and collected 470 copies, with a return rate of 100%. After eliminating the invalid samples, there were 453 valid samples, with a valid return rate of 96.3%. We distributed questionnaires at outside the fitness clubs in Taichung City from May 20th to June 13th, 2016. The study’s results indicate that value co-creation attitude, value co-creation subjective norm, and price affordability have positive effects on value co-creation behavior; value co-creation behavior has a positive effect on customer loyalty, and regular behavior has a negative moderating effect on the influence of value co-creation behavior on customer loyalty.